No Defibrillation Testing Best for ICD Implantation - Hitt, Emma (MD Conference Express, 2014)
Defibrillation testing does not improve the efficacy of first shock after implantable cardioverter defibrillator (ICD) placement, nor does it decrease all-cause mortality. This article presents data from the Shockless Implant Evaluation trial [SIMPLE; NCT00800384].